PROYECTO DE FACTIBILIDAD PARA LA CONSTRUCCIÓN DE UN EDIFICIO DE ESTACIONAMIENTO VEHICULAR EN LA CIUDAD DE CARIAMANGA - Ludeña Oviedo, Rosario Tatiana (2015)
Our country cross low economic growth due to lack of business development, therefore career as a student of Business Administration from the National University of Loja and a requirement for the degree of Engineer in Business Administration have seen fit conduct research called "PROJECT FEASIBILITY FOR THE CONSTRUCTION OF A VEHICLE PARKING BUILDING IN THE CITY OF CARIAMANGA". The present work aims to provide a solution to the lack of spaces where the owners of the vehicles, safety and comfort for these is offered, as well as contribute to the socioeconomic growth of the city, creating new jobs better service the inhabitants of the same, as well as setting an example of entrepreneurship and bridle quality services, in the same way make the necessary studies to determine whether the project in question, its operation is feasible for which we proceed to make the different studies such as Market Research, Technical Study, Finance and Financial Evaluation Study with which we develop and determine the feasibility of the project. After analyzing each of the studies it was determined that the project in question is feasible for the city of Cariamanga since it is very necessary that vehicles are organized and there are fewer accidents vehicular disorder. In the study of market demand it is determined for this project which is an acceptance of 76.90 % of the population of the owner of the vehicle fleet Cariamanga city. 6 Likewise with the technical capacity that will study the parking lot, considering that the average number of times an owner parked the car in an hour it is twice the annual capacity is 202 752 services will , and likewise ends physical infrastructure which consists of an area of 320 sqm on the first floor 23 spaces and two offices for management and a bathroom and on the second floor 25 and space for a total of 48 spaces. In the law firm the company is incorporated as a limited liability company under the name of vehicular parking service " Cariamanga CITY " . In the economic study contains all those items of fixed assets, deferred assets and current assets with which to begin the operation of the company and taking an investment of $ 194,968.13 . The financial evaluation determined the feasibility of the project for purposes of this thesis is the NPV values of $ 141,059.53 which determines the feasibility of it likewise IRR is 23.31% this determines the profitability. The cost benefit ratio is 0.61 cents for every dollar invested , which in turn requires four years six months and 14 days to recover the investment . Finally it was determined that the project is not sensitive to changes and with increased costs of 68.25% remains unchanged and also with a decrease in revenue of 28.85 % also unchanged. Once the research process has been completed it is determined that the feasibility project is profitable and can start with security because it has obtained favorable and positive results in all studies so its implementation is recommended.